Spatiotemporal analysis of land-use change and its impact on surface runoff in Tsushima Island, Japan - Tallar, Robby Yussac; Mauregar, Golan Geldoffer; Hirose, Eishi (Frontiers in Environmental Science, 2024)
Previous research on watershed assessments has primarily emphasized general hydrological or technical findings, neglecting the spatiotemporal analysis of land-use change and its influence on surface runoff. This study addresses this gap by using a geographic information system (GIS)-based method to analyze surface runoff variations due to land-use change on Tsushima Island, Japan. By leveraging spatiotemporal analysis within a GIS framework, the study interprets satellite imagery (Landsat 8 data, 2014–2024) to assess land use and watershed characteristics. This approach culminates in a comprehensive map depicting potential flood risk across the island. In conclusion, this study offers an advanced method for communicating potential flood risks to the public and policymakers, enabling proactive mitigation strategies for the coming decade.